DNA aptamer immobilized hydroxyapatite for enhancing angiogenesis and bone regeneration. (November 2019) - Son, Jaewoo; Kim, Junhyung; Lee, Kyungwoo; Hwang, Jangsun; Choi, Yonghyun; Seo, Youngmin; Jeon, Hojeong; Kang, Ho Chang; Woo, Heung-Myung; Kang, Byung-Jae; Choi, Jonghoon
Graphical abstract: Abstract: In this study, we developed aptamer-conjugated hydroxyapatite (Apt-HA) that promotes bone regeneration and angiogenesis. The 3R02 bivalent aptamer specific to vascular endothelial growth factor (VEGF) was grafted to the hydroxyapatite (HA) surface. Apt-HA was tested for its VEGF protein capture ability to determine the optimal aptamer concentration immobilized on the HA. Apt-HA showed higher VEGF protein capture ability, and faster growth of human umbilical vein endothelial cell (HUVEC) compared to a neat HA with no cytotoxic effects on human osteoblasts. To examine in vivo angiogenesis and bone regeneration, Apt-HA and HA were bilaterally implanted into rabbit tibial metaphyseal defects and analyzed after eight weeks using micro-CT, histology, and histomorphometry. Apt-HA showed significantly increased the volume of new bones, the percentage of bone, and the density of bone mineral in cortical bone. Apt-HA also exhibited the enhanced bone formation at the cortical region in a histomorphometric analysis. Finally, Apt-HA showed significantly increased blood vessel number compared to a neat HA. In summary, the engineered Apt-HA has potential as a bone graft material that may simultaneously promote bone regeneration and angiogenesis. Statement of Significance: This work presents a functional hydroxyapatite bone graft using a DNA-based aptamer which overcomes the limitations of existing bone graft materials, which use bound signaling peptides. DNA aptamer immobilized hydroxyapatite enhances the in vitro proliferation of human umbilical vascular endothelial cells as well as in vivo angiogenesis and bone regeneration. DNA aptamer immobilized hydroxyapatite shows no cytotoxic effect on human osteoblasts.